1997
DOI: 10.1042/bj3270747
|View full text |Cite
|
Sign up to set email alerts
|

Tetramerization domain of human butyrylcholinesterase is at the C-terminus

Abstract: Butyrylcholinesterase (BChE) in human serum consists predominantly of tetramers. Recombinant BChE, however, expressed in Chinese hamster ovary (CHO) cells, consists of approx. 55% dimers, 10-30% tetramers and 15-40% monomers. To determine the origin of the monomer species we added the FLAG epitope (epitope tag, amino acid sequence DYKDDDDK) to the C-terminus of the enzyme, and expressed BChE-FLAG in CHO cells. We found that secreted, active monomers had lost their FLAG epitope, suggesting that the monomers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 43 publications
9
98
0
Order By: Relevance
“…Although the product was truncated close to the COOH terminus (80% of full length), enzyme function was unlikely because deletion constructs have shown a 525-amino acid polypeptide is the minimum length for BChE compatible with function (19 ). Pedigree studies on the patient's two daughters indicated both are carriers of the N106FS-insA but not R424X (Fig.…”
Section: Results From Bche Sequencing Including New Mutationsmentioning
confidence: 99%
“…Although the product was truncated close to the COOH terminus (80% of full length), enzyme function was unlikely because deletion constructs have shown a 525-amino acid polypeptide is the minimum length for BChE compatible with function (19 ). Pedigree studies on the patient's two daughters indicated both are carriers of the N106FS-insA but not R424X (Fig.…”
Section: Results From Bche Sequencing Including New Mutationsmentioning
confidence: 99%
“…BuChE is a tetrameric glycoprotein composed of four subunits. Both dimeric and monomeric forms are stable and ubiquitous in the body 29 . All subunits are identical and composed of 574 amino acids with an overall molecular weight close to 85 kDa.…”
Section: Butyrylcholinesterasementioning
confidence: 99%
“…The Assembly of AChE or BChE Homodimers-Both AChE T and BChE T possess a cysteine residue near the C-terminal extremity of their t-peptide; this residue has been found to participate in the formation of disulfide-linked dimers in asymmetric AChE (28,34) and in the human BChE G 4 form (13). In addition, mouse PRiMA I contains four cysteines upstream of the PRAD (Cys 6 , Cys 13 , Cys 17 , and Cys 19 in the mature protein) (25), which may form disulfide linkages with associated catalytic subunits.…”
Section: Formation Of Prima-linked Achebche G 4 Hybrids In Transfectedmentioning
confidence: 99%